Expressive Timing and Tempo Variance in Six Landmark Recordings of Villa-Lobos' Etude No. 1: A Sonic Visualizer-Based Computational Analysis - Djahwasi, Herry Rizal; Sampurno, Muchammad Bayu Tejo; Nazeri, Nazimin (Institut Seni Indonesia Yogyakarta, 2025)
In contrast to the extensive research conducted on piano and violin, there have only been two studies focused on classical guitar that utilize computer-based recordings of performers. This study presents a performance recording of Villa-Lobos' Etude No. 1, focusing on the extraction of expressive elements in musical performances through visual audio analysis. which comparing from six important figures on classical guitar performer. The first phase of investigation involves a thorough examination and quantification of the interpretative variances in tempo and intensity attributes among six distinguished classical guitarists' recordings of Villa Lobos' Etude No. 1, employing computer-based sonic visualizer performance analysis tools. The second phase of investigation involves identifying and documenting the unique stylistic patterns inherent in each guitarist's interpretation of Villa Lobos' Etude No. 1. The data performance recording utilized a sonic visualizer to generate a specific tempo curve. The model and parameters of musical expression developed by structured and un-structured musical expressive timing. The variance in tempo and intensity attributes among six virtuoso classical guitarists' recordings of Villa Lobos' Etude No. 1 reveals notable differences in their musical expressive timing. The finding of this study demonstrates the importance of the literature of music performance is equally true in the form of the literature of musical structure and the literature of music history.